Transaksi di Bursa Efek Perspektif Islam (Studi Kasus di Aplikasi Bibit): Studi Kasus Aplikasi Bibit - Wardiman, Rohmat; Jamal Abdul (Jurnal Ilmiah Ekonomi Islam, 2026)
This article discusses the construction of contracts in sharia capital market practices in Indonesia, focusing on a case study of the Bibit application as a financial technology-based mutual fund selling agent. This research uses a literature study method to examine the principles of contemporary muamalah jurisprudence that form the basis of digital transactions, specifically the wakalah bil ujrah and mudharabah contracts. The analysis shows that the sharia capital market mechanism in Indonesia operates with a multi-layered supervisory system through the Financial Services Authority (OJK), the National Sharia Council (DSN-MUI), and the Sharia Supervisory Board (DPS), and applies qualitative and quantitative screening to ensure the halal status of investment instruments. In the context of Bibit, the wakalah bil ujrah contract applies between the investor and the application as an intermediary, while the mudharabah contract applies between the investor and the sharia investment manager as the fund manager. The validity of digital contracts is recognized through the concept of ijab qabul hukmi, with the requirement for information transparency to minimize elements of gharar and maysir. The research results state that investment practices through Bibit are in accordance with sharia principles, although the challenge of investor education still needs.